(untitled) (Global Journal of Science Frontier Research, 2018)
Biostimulatory effects of cow dung on some fungal biodegradation of atrazine. This work was designed to investigate the effect of using a biostimulant (cow dung) on some fungal strains for the possible degradation of atrazine-contaminated soil. The physicochemical characteristics of the soil and cow dung were determined using standard methods. The effects of pre and post biostimulation of fungal species were carried out using enumeration techniques. Fungal strains such as Trichoderma harzianum and Aspergillus niger were identified based on macroscopic and microscopic identification. Atrazine degradation was monitored by assaying the enzymes involved in the degradation and its metabolites using GC-MS techniques. The results of the soil physicochemical characteristics showed slightly acidic pH (6.7±0.99), moderate calcium (6.3±0.19Cmol/kg), high magnesium (5.10±0.38 Cmol/kg), moderate potassium (0.48±0.02 Cmol/kg, low sodium (0.15±0.01 Cmol/kg), moderately low nitrogen (0.16±0.01g/kg), moderate phosphorus (12.22±1.45 g/kg), high O.C(15.38±0.05 g/kg) were obtained respectively.